Awareness of Environmental Issues Among Consumers in the Malaysian Hotel Industry - Yusof, Dr. Yusnita; Ibrahim, Prof. Datuk Dr. Yahaya; Awang, Prof. Dr. Zainudin (IGI Global Business Science Reference (an imprint of IGI Global), 2017)
Global issues such as climate change, global warming and pollution have become some of the most critical issues happening around the world for quite some time. Previous research has found that the environmental issues are closely linked with human activities. Generally, the hotel industry is closely related to the environment, particularly through daily operations that can lead to these environmental issues. Beginning a few decades ago, there was an increase in environmental awareness in the hospitality industry. In this light, green hotels seem to be becoming a growing niche in the competitive lodging industry and the number of customers who are interested in staying at green hotels has also increased. Due to the lack of studies that explore the green efforts that influence customer satisfaction and customer loyalty, this study was therefore conducted to investigate the effect of environmental management practices towards customer satisfaction and customer loyalty in the Malaysian hotel industry.